Molecular Mechanisms and Toxic Effects of Ketamine - ZUO Yu-meng; HAN Wei; ZHANG Jian-bo; LI Tao (Fayixue Zazhi)
Ketamine is a dissociative anesthetic. It is clinically used as a surgical anesthetic or anesthetic inducer and has a certain degree of mental dependence. Its abuse can lead to nerve damage, adverse emotional reactions and other toxic side effects. The primary mechanism by which ketamine exerts its pharmacological effects is to block N-methyl-D-aspartate receptors （NMDAR）. It also functions through pathways such as α-amino-3-hydroxy-5-methyl-4-isox-azolepropionic acid receptors （AMPAR）, opioid receptors, γ-aminobutyric acid （GABA） receptors, monoaminergic receptors, cholinergic receptors, hyperpolarization-activated cyclic nucleotide-gated （HCN） channels, voltage-gated sodium channels, and L-type voltage-dependent calcium channels （VDCC）. This article summarizes the molecular mechanism and toxic effects of ketamine’s pharmacological functions, in order to provide a basis for forensic applications such as the identification of symptomatic phenotypes of ketamine toxic effects and the identification of ketamine abuse.